The economics of organized crime : evidence on FDI attraction in Latin America and Caribbean - Tošovský, Štěpán (2016)
This paper attempts to investigate the degree to which organized crime affects FDI in 15 Latin America and Caribbean countries during 2006-2014 period. We employed four crime proxies: homicide rate, organized crime index, business cost of terrorism index and business cost of crime index and analyzed their impact on overall, sectoral and industrial FDI inflows. We find evidence of a deterrent effect of organized crime on FDI inflows; in particular on FDI in secondary and tertiary sectors. On the contrary FDI inflows in more extractive industries - primary sector - are less affected by the presence of organized crime